#### Answer

$\{(-1,1)\}$

#### Work Step by Step

1. The least work in creating opposite coefficients is to multiply the second equation by ($-2)$ , which will lead to eliminating x
$\left\{\begin{array}{lll}
4x & +3y & =-1\\
-4x & -10y & =-6
\end{array}\right.$
2. ... add the equations and solve
$-7y=-7\qquad/\div(-7)$
$y=1$
3. Back-substitute into one of the initial equations
$4x+3y=-1$
$4x+3(1)=-1$
$4x=-4\qquad/\div 4$
$x=-1$
4. Write the solution as an ordered pair.
Solution set: $\{(-1,1)\}$